Global maternal health country typologies: A framework to guide policy. - Zachary J Ward; Rifat Atun; Gary King; Brenda Sequeira DMello; Sue J Goldie (Public Library of Science (PLoS), 2024)
Maternal mortality remains a large challenge in global health. Learning from the experience of similar countries can help to accelerate progress. In this analysis we develop a typology of country groupings for maternal health and provide guidance on how policy implications vary by country typology. We used estimates from the Global Maternal Health (GMatH) microsimulation model, which was empirically calibrated to a range of fertility, process, and mortality indicators and provides estimates for 200 countries and territories. We used the 2022 estimates of the maternal mortality ratio (MMR) and lifetime risk of maternal death (LTR) and used a k-means clustering algorithm to define groups of countries based on these indicators. We estimated the means of other maternal indicators for each group, as well as the mean impact of different policy interventions. We identified 7 groups (A-G) of country typologies with different salient features. High burden countries (A-B) generally have MMRs above 500 and LTRs above 2%, and account for nearly 25% of global maternal deaths. Countries in these groups are estimated to benefit most from improving access to family planning and increasing facility births. Middle burden countries (C-E) generally have MMRs between 100-500 and LTRs between 0.5%-3%. Countries in these groups account for 55% of global maternal deaths and would benefit most from increasing facility births and improving quality of care. Low burden countries (F-G) generally have MMRs below 100 and LTRs below 0.5%, account for 20% of global maternal deaths, and would benefit most from improving access to family planning and community-based interventions and linkages to care. Indicators vary widely across groups, but also within groups, highlighting the importance of considering multiple indicators when assessing progress in maternal health. Policy impacts also differ by country typology, providing policymakers with information to help prioritize interventions.